Anatomy, microstructure, and endogenous hormone changes in Gnetum parvifolium during anthesis. Issue 1 (24th August 2017) - Lan, Qian; Liu, Jian‐Feng; Shi, Sheng‐Qing; Deng, Nan; Jiang, Ze‐Ping; Chang, Er‐Mei
Abstract: The study of the sexual systems of plants is very important for understanding their evolutionary process. Gnetum is a pivotal species in comprehending the seed plant phylogeny. However, the sexual systems of this genus are not fully understood. To investigate the sexual system of Gnetum, the anatomical structure, microstructure, and endogenous hormones were investigated from the differentiation of flower buds to fertilization in the floral organs of female and male of G. parvifolium (Warb.) C.Y. Cheng, widely distributed in the north of China. After 2 years of field investigations, the staminate strobili were observed on female plants for the first time and the abortive ovules were also found on male plants. In addition, high levels of gibberellin A3 and zeatin riboside led to masculinization, whereas a high level of indole‐3‐acetic acid favored feminization. A comprehensive analysis of the results indicates that G. parvifolium may not be completely dioecious on morphology, but female and male plants can only perform their own gender function, which would provide a better understanding of the diversity of sexual systems in Gnetum, and reproductive structures of seed plants.